(untitled) (Journal of Astronomy & Earth Sciences Education, 2016)
There has been considerable debate in recent years—some well informed and others not so well informed—about the advantages and disadvantages of publishing in online, open-access journals as compared to traditional, subscription-based, print journals. For many professional societies, traditional, subscription-based, page-charge funded, print journals have served as an important service that societies can enthusiastically provide to their members, as well as provide societies with a healthy stream of financial revenue. At the same time as providing revenue to run a society, society members have been able to provide important service to the broader professional community by publishing their own scholarship and conducting peer reviews of others’ research. By far, the majority of a journal’s cost has been born by libraries paying hefty subscription fees.